Modelling and simulation of water-based hydraulic hybrid driveline - Saiful Akmal Sabaruddin (2018)
Typical hydraulic hybrid system vehicles depend on oil-based hydraulic fluid. Due to the natural concerns of environment and safety, promote the uses of the water-based hydraulic hybrid system. The main focus of this thesis is to investigate the potential of using water-based hydraulic technology instead of the current oil-based hydraulic technology. The main subject of this technology is in heavy commercial vehicles that frequently in a stop and go modes such as garbage trucks or delivery trucks that produce an immense amount of energy in a moment. The hydraulic hybrid driveline presented in this research is a series type, and the output of the driveline is connected to a Mitsubishi Fuso 6D34-0AT2 as a load to the system. In addition, the driveline is contained of hydraulic component (accumulator, hydraulic pump/motor) which serves to store and distribute power. HyspinAWS68 (mineral oil) was used as a pressure medium to create a comparison with water. This research includes an extensive study on the component modeling and simulation by using Matlab/Simulink and mainly based on the platform of Simhydraulics for the hydraulic flow and Simdriveline for the mechanical line. The focus part of modeling is primarily at 4 parts of the driveline which is system pressure, volumetric displacement, total accumulator volume, high-pressure accumulator pre-charge pressure. Based on the simulation, several data were collected such as time taken to fully charged, pressure, volumetric flow rate, torque, power, vehicle speed and also efficiency. The simulation result indicates that as one might expect that HyspinAWS68 has a higher performance of hydraulic hybrid driveline compared to water. This is due to the weakness of water properties as a pressure medium in terms of the density, viscosity, bulk modulus that causes a significant effect on the efficiency and performance of the hydraulic hybrid driveline. Several serious issues faced by water are internal leakage, pressure drop and also the capability to be compressed. In spite of this, the implementation of water hydraulic a potential response that required a depth study in terms of the properties and the component parameter to achieve the optimum performance of water-based hydraulic hybrid driveline. In future, experimental research on the performance of water-based hydraulic hybrid is required.